Bringing transnational families from the margins to the centre of family studies in Britain - Reynolds, Tracey; Zontini, Elisabetta (Policy Press, 2014)
Britain, alongside other Western contemporary societies, has undergone important social and demographic transformations resulting from increased migration. One important change is that family life is increasingly practised across national borders. Research within the field of migration studies, has been pivotal in highlighting the maintenance of family networks across national borders and geographical distance. Yet, rather surprisingly, a detailed analysis of family relationships that are practised across international borders is a marginal field of enquiry within British family studies. In this article, therefore, we argue the case for bringing transnational family studies in to the 'mainstream' academic field of family studies in Britain. We do so by drawing on examples from our respective studies on Caribbean and Italian transnational family relationships to (re)frame concepts typically associated with British family studies, such as for example the 'normative family', everyday practices involved in 'doing family' and the notion of 'families of choice'.